Writing Nouns in English as a Foreign Language: A Cross-Sectional Study of Their Acquisition Process - Campos Estarás, Begoña (2024)
Before the arrival of the communicative approach in our classrooms, the teaching and the learning of vocabulary was based on memorising lists of words in written form. From then on, students had to learn how to pronounce them. This resulted in correct spelling and poor pronunciation. With the introduction of the communicative approach, the focus has been on oral learning of vocabulary and thus pronunciation has improved, but correct spelling has been lost in many cases. In this paper we present the results of a cross-sectional study of errors and correct productions of nine nouns at the end of primary, compulsory secondary and baccalaureate education. For this purpose, we have used a corpus created in the Canary Islands, representative of the students of the seven islands, which includes a sample of essays written in English. The results show a decrease in errors. In conclusion, we can see that most of the errors are of an intralinguistic type, being mostly writing hypotheses that the pupil uses in order to internalise the process of reading and writing in English.